Utrata płynności a utrata wypłacalności - Wyrobek, Joanna (Differences Between the Loss of Liquidity and Insolvency, 2008)
The purpose of this paper was to analyze similarities and differences between the loss of financial liquidity and insolvency of the firm. The comparison between liquidity and solvency held in this paper proves that the definition of liquidity is multidimensional and it is not easy to decide when the firm lost liquidity. There are many factors that have to co-occur to let one determine when the firm lost its ability to meet obligations, such as: liquidity ratios, the overall financial situation of the firm, and the fact that it does not pay its liabilities in time. None of these factors taken separately is sufficient to judge as to when the firm lost liquidity, they must be analyzed jointly.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 615-622